Viable Disposal of Post-Consumer Polymers in Mexico: A Review - Ángeles-Hurtado, L.A.; Rodríguez-Reséndiz, Juvenal; Salazar-Colores, Sebastián; Torres-Salinas, Hugo; Sevilla-Camacho, P. Y. (Frontiers in Environmental Science, 2021)
Post-consumer polymers require viable actions to transfer value to the final consumer to reduce environmental impact. Worldwide, initiatives are being developed to promote the culture of recycling and thus reduce waste generation. These initiatives seek to make the work of thousands of people visible, encourage job creation, and promote businesses through incentive schemes for effective separation, collection, classification, reuse, and recycling, in the hands of consumers, collectors, and scavenges. It is necessary to emphasize that Mexico needs to develop techniques to increase the productivity of collection centers for recyclable materials and to face the challenges that recycling implies. For these reasons, the Mexican government has spoken of waste management as a national priority due to the COVID-19 pandemic, which increased urban solid waste between 3.3 % and 16.5 % in addition to what was generated under normal conditions. Also, the recycling chain provides economic income to more than 35 thousand Mexicans. Polyethylene terephthalate (PET) is an example of the most notable circular economy in Mexico because 60 % of PET bottles are recycled. Therefore, this article addresses the methods and systems in the management of urban solid waste. It focuses on post-consumer recycled plastic bottles to provide an overview of cost-effective strategies for designing and developing an affordable sorting system in Mexico from the academic field. In addition, to simplify the solution that we propose, it is recommended to combine optical techniques such as infrared spectroscopy and Raman spectroscopy with others methods that work together, such as computer vision, to develop affordable systems that address the limitations of mechanical systems.